Extension Officers’ Adoption of Modern Information Communication Technologies to Interact with Farmers of Trinidad - Lendel K. Narine; Amy Harder; Grady T. Roberts (Journal of International Agricultural and Extension Education, 2019)
The Ministry Extension struggled to provide adequate services to Trinidadian farmers because of a reliance on top-down methods. Information Communication Technologies (ICTs) have been touted as an effective and efficient way to serve farmers in the Caribbean. This study sought to describe the factors affecting Ministry Extension officers’ decisions to adopt text messaging via Short Messaging Service (SMS) to communicate with farmers. The Diffusion of Innovation theory (Rogers, 2003) guided this study, and data were collected from a census of Extension officers in the Ministry Extension service. Results showed most Extension officers used voice calls and SMS to communicate with farmers. Many Extension officers who did not use ICTs were willing to use multimedia messaging, SMS, electronic mail (email), voice calls, and social media to interact with farmers. Extension officers were accustomed to using text messaging, saw the benefit of using SMS to communicate with farmers, and were confident in their ability to use SMS for farmer interactions. However, results indicated a lacking policy environment for SMS use, and limited support existed from peers and supervisors to use SMS to interact with farmers. Findings showed most Extension officers perceived farmers can use mobile telephones to make calls, send text messages, and use multimedia messaging. This implies Extension officers were aware of the potential for using a variety of ICTs to engage with farmers. However, internal policies and administrative support are critical to their adoption of ICTs for farmer interactions in Extension
Keywords: communication; extension methods; farmer interactions; Information Communication Technologies; Short Messaging Service